Determinación de las competencias organizacionales en la empresa Genética Nacional S.A. del cantón Montecristi - Párraga Vergara, Jessenia Betzabeth (2019)
The present investigation was based on determining the organizational competencies of the national genetic company SA, located in the city of Montecristi, for this the three-phase programming was carried out, where the company was characterized to know the current situation, an interview was conducted where it was possible to know if the poultry knows about the organizational competencies in such a way a characterization sheet was applied in order to improve its corporate social responsibility, in this way a bibliographic review of those competencies suitable for this type of company was carried out, to The selection of experts needed an evaluation tool for the identification of the suitable experts for this study with which it allowed the validation of the results, in this way we worked with the Delphi methodology to determine them, thus being: Innovation, Training Learning Permanent, Biosecurity of the avian farm wave, Communication, integrated teamwork, Perseverance of the Environment, quality orientation, Customer orientation, once these skills were obtained, the application of the surveys to 140 employees was continued, to bequeath to an optimal response they were assigned a series of sub-indicators, in turn the database was developed with the respective answers for the determination of the descriptive statistics in the Excel, which allowed to know the degree of development that each competition obtained. Finally, an action plan was proposed that was based on an Ishikawa cause-effect diagram with the competencies that obtained a low level of development.